Evaluating the Use of Geotechnology and Multimedia Resources in Cartography Lessons for Environmental Studies - Sousa, Iomara Barros de [UNESP]; Di Maio, Angelica Carvalho; Sluter, C. R.; Cruz, CBM; DeMenezes, PML (Springer, 2015)
The free accessibility to satellite images and geographic information systems (GIS), along with students' ability in handling multimedia on their own smartphones, enable the use of geotechnologies and multimedia resources in cartography teaching. This research has considered the contributions, limits, and possibilities of employing space technology, geoprocessing, and multimedia resources in geography classes for 7th-grade students in a public schools, in Sao Goncalo city, Rio de Janeiro State, Brazil. Digital material has also been developed through the web, named Mapeando Meu Rio (MMR) or Mapping My River (MMR), which addresses the issue of the socio-environmental perception of the Alcantara river. The interest and involvement from the students throughout the different activities proposed on the mentioned material has been remarkable, especially in the use of multimedia resources and geotechnologies as a support material for environmental education. Based on the MMR evaluation, 7th-grade students have fallen short in their cartographic literacy at the end of their school year; this failure has been noticed both in their ability to make mental maps and in the handling of global positioning systems (GPS), Google Earth and ArcGIS Online. When requested to produce a spatial layout on their own, students were not able to use their basic knowledge of cartography, especially in the use of legends, geographical coordinates, and spatial orientation. Cartographic literacy should not be restrained to the syllabus of 6th-grade classes; instead, it should be considered as a means of communication to the understanding of the spatial dynamics during the whole course of elementary and high school. All geography-based activities are meant to give students a better understanding of their geographical space, in such a way that they may be able to build meaningful abstractions from their own reality-that is, from their own living place.
Keywords: Cartography for children; Geotechnologies; Socio-environmental perception